Rhesus macaques as a tractable physiological model of human ageing. (9th November 2020) - Chiou, Kenneth L.; Montague, Michael J.; Goldman, Elisabeth A.; Watowich, Marina M.; Sams, Sierra N.; Song, Jeff; Horvath, Julie E.; Sterner, Kirstin N.; Ruiz-Lambides, Angelina V.; Martínez, Melween I.; Higham, James P.; Brent, Lauren J. N.; et al.
Abstract : Research in the basic biology of ageing is increasingly identifying mechanisms and modifiers of ageing in short-lived organisms such as worms and mice. The ultimate goal of such work is to improve human health, particularly in the growing segment of the population surviving into old age. Thus far, few interventions have robustly transcended species boundaries in the laboratory, suggesting that changes in approach are needed to avoid costly failures in translational human research. In this review, we discuss both well-established and alternative model organisms for ageing research and outline how research in nonhuman primates is sorely needed, first, to translate findings from short-lived organisms to humans, and second, to understand key aspects of ageing that are unique to primate biology. We focus on rhesus macaques as a particularly promising model organism for ageing research owing to their social and physiological similarity to humans as well as the existence of key resources that have been developed for this species. As a case study, we compare gene regulatory signatures of ageing in the peripheral immune system between humans and rhesus macaques from a free-ranging study population in Cayo Santiago. We show that both mRNA expression and DNA methylation signatures of immune ageing are broadly shared between macaques and humans, indicating strong conservation of the trajectory of ageing in the immune system. We conclude with a review of key issues in the biology of ageing for which macaques and other nonhuman primates may uniquely contribute valuable insights, including the effects of social gradients on health and ageing. We anticipate that continuing research in rhesus macaques and other nonhuman primates will play a critical role in conjunction with the model organism and human biodemographic research in ultimately improving translational outcomes and extending health and longevity in our ageing population. This article is part of the theme issue 'Evolution of the primate ageing process'.